Training Features to Japanese Experience Constructive Use in Russia in Traditional Folk Cultures Pedagogical Potential Implementation - Korshunova, Irina V.; Fedotova, Elena L.; Kosogova, Anastasia S.; Podlinyaev, Oleg L.; Timoshenko, Aleksandr I.; Makarova, Inna A.; Shafranova, Olga E.; Kora, Nataliya A.; Schepkina, Neile K. (International Review of Management and Marketing, 2016)
The relevance of the study of this problem is reasoned by modern achievements of foreign countries (particularly Japan) in the traditional folk culture’s pedagogical potential implementation and insufficient knowledge in Russia of these achievements and possibilities application in modern Russian socio-cultural environment. In this regard, this article is aimed at the development and experimental validation of a system of cultural, leisure and educational activities in personnel training to use the Japanese experience of traditional folk culture’s pedagogical potential implementation in Russia. The leading methods to study this problem are theoretical: the analysis of philosophical, pedagogical, artistic, cultural, ethnological literature on the research topic; instructional design; empirical: an analysis of the experience of socio-cultural and educational institutions in the implementation of traditional folk culture’s pedagogical potential; observation; survey; experimental work. The article theoretically and experimentally justifies a complete system of cultural, leisure and educational activities for staff training to use innovative foreign (Japanese) experience of traditional folk culture’s pedagogical implementation in Russia. The materials of this article can be used in the activity of culture and education state management authorities; centers of folk arts and crafts, ethnic and cultural centers, cultural and leisure centers and other socio-cultural institutions and organizations; institutions of basic and professional education; societies of the Russian-Japanese friendship, other public organizations and associations. Keywords: Staff Training, Japanese Experience, Pedagogical Potential, Traditional Folk Culture. JEL Classifications: A23, I23, I26